(untitled) (Research, Society and Development, 2022)
The objective of this study is to present and analyze the evolution of Engineering Education in the periods of antiquity, medieval, modern and contemporary age. It was also accomplished to analyze in more detail the current contemporary society, its behavior, and its aspirations from a literature review. Through this analysis, some forms of established education in engineering were identified to be more confluent with the aspirations of the current society. It is observed today that formal education in Engineering is out of step with the world. It was concluded that the future of engineering education aims to prepare the student for three main challenges: sustainability, industry 4.0, and employability. To ready the world’s future engineering professionals, two perspectives must be considered; what skills students should acquire to better prepare for current challenges, and what new methods and techniques should be used in an education focusing on the student as the protagonist.